(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
ملخص هذا البحث يتناول بالدراسة موضوع: مسالك العلماء في الحكم بالنسخ في السنّة النبوية بين المعتدلين والمتساهلين. ويهدف البحث إلى الوقوف على مسالك العلماء في الحكم بالنسخ في السنة النبوية، وتمييز المتّفق عليه من المختلف فيه من تلك المسالك. وقد استخدم الباحث المنهج الاستقرائي التحليلي، والمنهج الاستنباطي الاستنتاجي. وانتهى البحث إلى عدد من النتائج أهمّها: أنّ المعتدلين من العلماء في هذا الباب هم الذين يقتصرون في الحكم بالنسخ على المسالك المتّفق عليها، وأمّا المتساهلون؛ فهم الذين يأخذون بالمسالك المختلف فيها، والتي تبيّن من خلال البحث أنها ليست مسالك للحكم بالنسخ على الراجح. كلمات دالة: مسالك – النسخ – السنة النبوية – المعتدلون – المتساهلون. Abstract This research deals with the study of a topic: The paths of scholars in ruling by alnasakh in the Sunnah of the Prophet between moderates and lenient. The researcher used the inductive analytical approach and deductive deductive approach. The research has concluded with a number of results, the most important of which are: that the moderate scholars in this regard are the ones who limit the ruling by alnasakh the agreed-upon paths, and as for the lenient ones; They are the ones who follow the different paths in which it has been shown, through research, that they are not paths for judging the most correct of alnasakh. Keywords: paths - alnasakh - the Sunnah of the Prophet - moderates - lenient.